A natureza jurídica do número 1 do Artigo 20º do Cód. VM e a sua interpretação - Castanheira, Rita Marques Murta Mendes (2016)
This reflection comes in the wake of a stage in the CMVM during which I was allowed to contact with the subject under consideration. Paragraph 1 of Article 20 of the Securities Code, a portion of standard, has generated some doctrinal doubts as to its best interpretation, as well as on their legal nature. As this provision, a portion of standard, that only conforms a legal norm as it relates to other portions of standards, one can not fail to meet the latest to respond to the issues raised. Since it is the transparency regime and the mandatory bids regime that have raised more doubts about the issues raised, in particular by the legal norms that determine the duty to communicate qualifying holdings and a mandatory bid, the provisions made by the Article 16 and Article 187 of the Securities Code must be analyzed in order to find answers to the questions raised. The mandatory bid will be highlighted because this has raised more questions within the doctrine. This is because: (i) the system of voting rights attribution was originally designed in European law to accommodate requirements of transparency and (ii) the interpretation of Article 20 paragraph 1, when related to the mandatory bid has been controversial.